(untitled) (Fiep Bulletin - online, 2013)
Goldenberg (2005, apud BOUDIE,1999), assured that the human image is associated with strong, powerful and manly beings and that the women are delicate, submissive, quiet. For Marsillac and Souza (2006 apud Welsch, 1995), it is considered inability to become different from the social established pattern, with no possibility of being the own choice. Meanwhile, following an “ideal” body pattern becomes a torture in chase of the acceptance and perfection. Facing such facts, the present study rises data to help identify the differences between the genders about aesthetics concerns, as relating them to the level of satisfaction with the body image, involving students from students from Federal Technological Educational Center from Campos dos Goitacazes belonging to Post graduation lato - senso levels. The data gotten had been studied through descriptive statistics of percentage. 100 post graduating students were analyzed (PG). So, facing such results from this search, we could set the existence of difference between the genders; being the female made of a more stereotyped aesthetics concern and a higher worry about looking slim, producing a sensation of feeling bad with the own image. And the male sex, despite showing a static pattern which matches the social dictation, presents lower indication of disagreement with the own body.